A study and analysis of love conceptualization approaches in the poems of Yadollah Behzad Kermanshahi - Hashem Karami; Nasrin Aliakbari; zaniar naghshbandi (مطالعات زبانی و بلاغی)
The present study examines and analyzes approaches to conceptualization of love in the work of contemporary poet Yadollah Behzad Kermanshahi. Adopting the method of description and analysis of data and relying on foundations of conceptual metaphor, this study tries to discover the hidden layers of imagery through identifying and analyzing the source domains of the metaphors   and to explore the thoughts predominating over the poet’s worldview. The results indicate that Behzad uses a wide variety of source domains such as anthropomorphism, reification, foodification, spatiality, elements in nature, health and illness, heat and light, shackles and imprisonment, sacred tasks and affairs, and schemas related to journey and direction. It must be noted that the hidden layers of these images entail positive meaning and concepts of love to the extent that, even when the poet uses negative source domains, his view of love is still positive and reassuring. Therefore, it could be stated that the poet assesses love with an absolutely affirmative worldview, considering it as a miracle that is the essence and delight of life and gives rise to hustle and bustle and fruitful activities in the world.